Shell elastic element with cut for drilling shock absorber - A.S, Velychkovych; T.M, Dalyak; Vo Duc, Anh (Petrovietnam Journal, 2017)
The study presents an initial design of the drilling shock absorber, developed on the basis of building a verified digital model of shell damper with the cut and using the algorithms of solution of the contact problems taking into account friction on contact surfaces. The overall picture of the stress-strain state of the elastic element of shell shock absorber is analysed. Structural strength is estimated using energy criteria. The hysteresis loops are constructed and analysed for a number of cyclic loading of the elastic element. The study results therefore allow assessment of the effect of the elastic properties of materials and the shell filler, their geometric parameters and tribological properties on the operating parameters. This enables more efficient use of the drilling facilities and improvement of the design of shell shock guards for maximum compliance with the criteria and the required level of damping, thus creating the preconditions for development of new technical solutions and design for systems of vibration protection.